p53 in Bronchial Club Cells Facilitates Chronic Lung Inflammation by Promoting Senescence - Adi Sagiv (Cell Reports, 2018)
Summary: The tumor suppressor p53 limits tumorigenesis by inducing apoptosis, cell cycle arrest, and senescence. Although p53 is known to limit inflammation during tumor development, its role in regulating chronic lung inflammation is less well understood. To elucidate the function of airway epithelial p53 in such inflammation, we subjected genetically modified mice, whose bronchial epithelial club cells lack p53, to repetitive inhalations of lipopolysaccharide (LPS), an exposure that leads to severe chronic bronchitis and airway senescence in wild-type mice. Surprisingly, the club cell p53 knockout mice exhibited reduced airway senescence and bronchitis in response to chronic LPS exposure and were significantly protected from global lung destruction. Furthermore, pharmacological elimination of senescent cells also protected wild-type mice from chronic LPS-induced bronchitis. Our results implicate p53 in induction of club-cell senescence and correlate epithelial cell senescence of chronic airway inflammation and lung destruction. : Sagiv et al. find that senescence and p53 in bronchial epithelial cells promote chronic lung inflammation and COPD-like disease. Genetic or pharmacological reduction in senescent cell number blunts chronic inflammation and limits disease progression. Keywords: cellular senescence, p53, bronchitis, inflammation, club cells